Temperature-Dependent Properties of Graphene on SiC Substrates for Triboelectric Nanogenerators - Wang, Sen; Wan, Lingyu; Li, Ding; Chen, Xiufang; Xu, Xiangang; Feng, Zhe Chuan; Ferguson, Ian T. (Frontiers in Materials, 2022)
Graphene has excellent properties such as ultra-high electrical conductivity, high carrier mobility and thermal conductivity, with a promising application in the field of Triboelectric nanogenerators (TENGs). We present a systemic investigation to explore structural, optical and temperature-dependent properties of single- and bi-layer graphene on SiC substrates, prepared by decomposition of SiC and transferred substrate methods, as well as their applications in TENGs. Compared to the transferred graphene onto SiC substrate, graphene grown by decomposition of SiC has better crystalline quality and surface morphology, fewer impurities, and a more stress effect between graphene and substrate. It also exhibited a longer correlation length of Raman phonons, impling better crystalline perfection. With the increase of temperature, the phonon correlation length, L, increases synchronously with the average length, Ld, of the point defect, as well as an increase in TENG outputs. Among them, the TENG with a bi-layer graphene grown by decomposition of SiC showed the best performances, especially at high temperature. These studies provide an essential reference for further application of graphene on SiC substrate in TENG-based devices.